Unearned income and labor supply: Evidence from survivor pensions in Austria - René Böheim; Michael Topf (Johannes Kepler University of Linz, Department of Economics, 2020)
We study the effect of lower unearned income on labor supply. To identify the causal effect of an unexpected reduction in unearned income, we exploit a policy reform that lowered survivor pensions in Austria. Men widowed after the survivor pension reform received an approximately 34% lower survivor pension than men widowed before the reform. We follow the employment history of both groups for 150 months and estimate the reform's effect on labor supply using a regression discontinuity design. The effect of the lower pension is evident immediately after the death of their spouse, is persistent over time, becomes more pronounced over time, and is robust across model specifications. Our baseline result suggests a 3.5 to 5.4 percentage point higher employment rate for survivors in the low pension regime in the long run. The estimated effect corresponds to a labor supply elasticity at the extensive margin with respect to the changes in total income of about -0.9 to -1.3.
Keywords: I38; J22; J48; 330; labor supply; unearned income; regression discontinuity design